Bibliometric Analysis of the Financial Supply Chain in the Palm Oil Industry - Judijanto, Loso (West Science Interdisciplinary Studies, 2025)
The palm oil industry plays a vital role in global agribusiness, with its financial supply chain increasingly recognized as a critical determinant of operational efficiency, sustainability, and inclusivity. This study conducts a bibliometric analysis to systematically map the academic literature on financial mechanisms within the palm oil supply chain. Using data from the Scopus database and visualization tools such as VOSviewer, the research identifies key themes, influential authors, institutional collaborations, and country-level networks from 2000 to 2025. Findings reveal that central concepts like palm oil, sustainable development, and biomass dominate the discourse, while emerging topics such as smallholder financing, deforestation, and green investment reflect shifting priorities toward sustainability and inclusive finance. Malaysia and Indonesia lead in research output, with strong global collaborations involving institutions in the United Kingdom, the United States, and the Netherlands. This study contributes to the theoretical understanding of the financial supply chain as a multidimensional construct influenced by environmental, economic, and social factors. It also offers practical insights for policymakers, financial institutions, and industry stakeholders aiming to align financial innovation with sustainable palm oil development.